Application of Environment-Based Discovery Learning Models to Improve Students Learning Outcomes in Class V Elementary School - Puspoarum, Mutiarasati (Universitas Sebelas Maret, 2022)
The purpose of this study is to improve the learning outcomes of grade V students on Ecosystem material at SD Negeri 1 Karangnongko for the 2021/2022 academic year through the application of an environment-based Discovery Learning model. The population of this study was all class V totaling 25 students. This study belongs to the type of classroom action research. The research method uses observation, test, interview, and documentation methods. Data analysis techniques use qualitative descriptive with data reduction, data presentation and conclusions. The test results showed that the students who completed the pre-cycle stage were 9 students or 36%. In cycle I students who completed it became 16 students or 64%, then in cycle II it increased to 21 students or 84%. Researchers concluded that the application of an environment-based discovery learning model can improve the learning outcomes of grade V students of SD Negeri 1 Karangnongko.